2024
DOI: 10.3390/jcm13030751
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Lipoprotein(a) Levels: Does a Specific Counseling Make Sense?

Federica Fogacci,
Valentina Di Micoli,
Pierre Sabouret
et al.

Abstract: Lipoprotein(Lp)(a) is a variant of low-density lipoprotein (LDL), bound to apolipoprotein B100, whose levels are associated with a significant increase in the risk of atherosclerosis-related cardiovascular events, but also to aortic stenosis and atrial fibrillation. Since plasma levels of Lp(a) are commonly considered resistant to lifestyle changes, we critically reviewed the available evidence on the effect of weight loss, dietary supplements, and physical activity on this risk factor. In our review, we obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 113 publications
(124 reference statements)
1
3
0
Order By: Relevance
“…The net benefit seems to be in favor of lp(a) lowering, via preservation of a reasonable SFA intake, despite marginal LDL-C increase. Our results are in line with expanding evidence, showing lp(a) increase with SFA reduction, and specifically with carbohydrate replacement [6][7][8][9][10][11]. Furthermore, in response to SFA increase: high density lipoproteincholesterol (HDL-C) increased as expected, and LDL particle size probably increased making them less atherogenic, as suggested by the decrease in triglycerides /HDL-C ratio [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The net benefit seems to be in favor of lp(a) lowering, via preservation of a reasonable SFA intake, despite marginal LDL-C increase. Our results are in line with expanding evidence, showing lp(a) increase with SFA reduction, and specifically with carbohydrate replacement [6][7][8][9][10][11]. Furthermore, in response to SFA increase: high density lipoproteincholesterol (HDL-C) increased as expected, and LDL particle size probably increased making them less atherogenic, as suggested by the decrease in triglycerides /HDL-C ratio [14].…”
Section: Discussionsupporting
confidence: 91%
“…This has limited research in this area and high-level evidence is lacking. Despite this, interest on this topic is rapidly expanding and data is continuously showing that although reducing SFA intake decreases LDL-C levels, it may increase lp(a) levels [6][7][8][9][10][11]. The recent European Atherosclerosis Society guidelines state that low SFA, high carbohydrate diets increase lp(a) by 10-15%.…”
Section: Introductionmentioning
confidence: 99%
“…Many other bioactive compounds have demonstrated efficacy as cholesterol-lowering agents in adults (red yeast rice, berberine, bergamot polyphenol fraction, and artichoke extracts), but not in children. Presently, no dietary supplements have been shown to significantly reduce lipoprotein (a) levels, beyond L-carnitine and Coenzyme Q10, but this effect has never tested in children [112].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown no significant changes, others have reported mild to moderate decreases in Lp(a) levels following exercise. The extent of change in Lp(a) levels may depend on factors such as age, the type, intensity, and duration of physical activity [ 59 , 158 ]. Overall, the impact of lifestyle modifications on Lp(a) levels is not fully understood and may vary among individuals.…”
Section: The Impact Of Lipid-modifying Interventions On Lp(a) Levels:...mentioning
confidence: 99%